Reconfiguring Da'wah Authorities in the Algorithmic Era: Generation Z's Cognitive Responses to Islamic Parenting Content on TikTok - Alif Mufid; Wahab Nur Kadri; Sahlul Fuad (Journal Research of Social Science, Economics, and Management, 2026)
The dissemination of Islamic da'wah has undergone a significant transformation with the rise of algorithm-mediated digital platforms, yet prior studies have often emphasized virality metrics while overlooking cognitive engagement and the reconstruction of religious authority. This study aims to examine how Generation Z audiences cognitively internalize and behaviourally respond to Islamic parenting content on TikTok, focusing on the account “Ayah Amanah” (@am.event). Employing a qualitative digital sociology approach, purposive sampling was used to collect video content and the top 21 audience comments per video. Data were analyzed through interactive thematic coding informed by Digital Religion Theory and Social Learning Theory. Findings reveal three major dynamics: first, religious authority is shifting from hierarchical validation to algorithmic authority, supported by engagement metrics and cyber religion marketing; second, audiences construct personalized piety and relational paternal identity, enhancing cognitive retention and self-efficacy; third, networked communities function as peer-support infrastructures, encouraging convergence of digital and offline religious practices. The study concludes that TikTok facilitates hybrid, participatory da'wah that lowers barriers to learning and promotes real-world application of ethical and spiritual practices. These results highlight the importance of critical digital religious literacy and ethical content curation for sustainable digital pedagogy.